(untitled) (Economic and Political Thought, 2014)
In the 21st century, India is more and more often perceived as a state with a growing political, economic and military potential, which together with China may dominate the international arena in the future. India started to accentuate its position in international relations 60 years ago so such a scenario would be its crowning achievement in its aspiration to be a superpower. The first Indian Prime Minister Jawaharlal Nehru’s policy of non-alignment, promotion of peace and world development in the 1950s aimed to establish India’s leadership. Although the priorities of India’s foreign policy were reformulated because of the changing regional and global conditions during the cold war (including the American-Pakistani-Chinese alliance), the state has never abandoned its aspirations to be a superpower. It should be remembered that contemporary strategy of India’s development is not only a result of reforms initiated in the 90s but also a legacy of the policy developed during the cold war, oscillating between idealism and realism.